Ecological Risk of Polychlorinated Biphenyls in Soil from Selected Residential Dumpsites in Delta State, Nigeria - Onojake, Lawson; Umudi, Ese Queen; Obukowho, Innocent Erhieyovwe; Nwakwanogo, Blessing Ese; Odo, Onyekachi Marcelus; Ugwu, Chioma Anthonia; Ehiedu, Chukwuwuikem Nathanael (FUDMA Journal of Sciences, 2026)
This study investigated the compositional patterns and ecological risks of polychlorinated biphenyls (PCBs) in soils from selected residential dumpsites in Delta State, Nigeria. Five soil samples were analyzed for 28 PCB congeners using gas chromatography–mass spectrometry (GC–MS) after Soxhlet extraction and clean-up with florisil and silica gel. The concentrations of ∑28 PCBs ranged from 6.88 to 21.25 ng/g, indicating contamination mainly associated with anthropogenic activities. The PCB profiles were dominated by penta-, tetra-, and hepta-chlorinated biphenyls, suggesting contributions from mixed waste sources such as domestic, industrial, electrical, and commercial materials. Ecological risk assessment based on Hakanson’s ecological risk index revealed varying degrees of environmental risk among the dumpsites. Dumpsite A showed low ecological risk, whereas dumpsites C and D exhibited considerable ecological risk levels. The toxic equivalency (TEQ) values of dioxin-like PCBs ranged from 0.007 to 0.104 ng TEQ/g and were below international guideline values, including the Threshold Effect Level (TEL), Probable Effect Level (PEL), and Effect Range Medium (ERM), indicating limited ecological effects. The study highlights the influence of poor waste management practices on PCB contamination and recommends regular monitoring, public awareness, and improved waste disposal measures to minimize environmental and psychological health in the affected communities
Keywords: PCBs; soil; dumpsite; ecological risk